Analysis of the Influence of Financial Report Accountability and Religiosity on Muzaki Trust in the Baitul Maal Hidayatullah (BMH) Institution in Bengkulu - HENDRI, HENDRI; Kurniawan ZP, Iwan (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to examine the effect of financial report accountability and religiosity on muzaki trust in the Baitul Maal Hidayatullah (BMH) institution in Bengkulu. Methodology: This research adopts a quantitative approach using multiple linear regression analysis. Data were collected through structured questionnaires distributed to 84 muzaki of BMH Bengkulu and analyzed after passing validity, reliability, and classical assumption tests. Results: The findings show that financial report accountability and religiosity have a positive and significant influence on muzaki trust. Greater transparency and accountability in financial reporting, supported by strong religious values, enhance donor confidence in zakat institutions. Novelty: This study integrates financial accountability and religiosity as complementary determinants of trust in Islamic philanthropic institutions. Findings: Financial accountability strengthens institutional credibility, while religiosity reinforces moral commitment and trust. Originality: The originality lies in providing localized empirical evidence from a regional zakat institution in Indonesia. Conclusions: Strengthening transparent financial governance and religiosity is crucial for sustaining muzaki trust. Type of Paper: Empirical Research Paper.